Success of In Vitro Fertilization: A Researched Science or a Performance Indicator - Salam, Mahmoud (2017)
Divisions of reproductive medicine often perceive the live birth rate (LBR) as the single most important performance indicator for any infertility clinic, and it reflects on the quality of their services. Due to this perception, some infertility experts might refrain from disclosing these rates in publications as a researched science. Infertility experts might not be familiar with the various methods of reporting LBR as an outcome of in vitro fertilization (IVF) and therefore should be aware of these methods. Moreover, infertility experts might miss to take into account some couple and disease-related characteristics that could be successful determinants of this LBR. This is a brief review on infertility and its impact on married couples, as well as the history and description of IVF. We also present infertility experts with various methods of reporting LBR and shed light on some of the couple and disease-related factors associated with higher LBRs after IVF as reported in literature